En Wallonie pendant la guerre. - Branquart, René (Braine-le-Comte : Lousse, 1919)
Bibliotheek E. Anseele
Dedicator: Branquart, René, dedicatee: Anseele, Edward (sr.)
Frans
Monografie
Keywords: Wereldoorlog 1